Advances in endovascular aneurysm management: coiling and adjunctive devices. Issue 1 (15th March 2020) - Campos, Jessica K; Lien, Brian V; Wang, Alice S; Lin, Li-Mei
Abstract : Endovascular coil embolisation continues to evolve and remains a valid modality in managing ruptured and unruptured cerebral aneurysms. Technological advances in coil properties, adjunctive devices and interventional techniques continue to improve long-term aneurysm occlusion rates. This review elaborates on the latest advances in next-generation endovascular coils and adjunctive coiling techniques for treating cerebral aneurysms.